2013
DOI: 10.1371/journal.pgen.1003812
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Dysregulation of Peptide Hormone Release in Mice Lacking Adaptor Protein AP-3

Abstract: The regulated secretion of peptide hormones, neural peptides and many growth factors depends on their sorting into large dense core vesicles (LDCVs) capable of regulated exocytosis. LDCVs form at the trans-Golgi network, but the mechanisms that sort proteins to this regulated secretory pathway and the cytosolic machinery that produces LDCVs remain poorly understood. Recently, we used an RNAi screen to identify a role for heterotetrameric adaptor protein AP-3 in regulated secretion and in particular, LDCV forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 61 publications
3
23
0
Order By: Relevance
“…Systemic loss of functional AP-3 causes endosomal trafficking defects, Hermansky-Pudlak syndrome, and neurological symptoms (Kantheti et al, 1998; Lane and Deol, 1974; Peden et al, 2002; Seong et al, 2005; Sirkis et al, 2013; Swank et al, 2000; Yang et al, 2000). These have mainly been ascribed to defects in lysosomal trafficking and/or biogenesis of LROs.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic loss of functional AP-3 causes endosomal trafficking defects, Hermansky-Pudlak syndrome, and neurological symptoms (Kantheti et al, 1998; Lane and Deol, 1974; Peden et al, 2002; Seong et al, 2005; Sirkis et al, 2013; Swank et al, 2000; Yang et al, 2000). These have mainly been ascribed to defects in lysosomal trafficking and/or biogenesis of LROs.…”
Section: Discussionmentioning
confidence: 99%
“…Sor4 expression is induced in coordination with SG proteins upon discharge of the mucocyst. One of these proteins, AP3, has recently been shown to be essential for the regulated secretion of insulin in β cells; β cells deficient in AP3 secreted insulin through the constitutive pathway (59,60). In Toxoplasma, deletion of the Vps10 homolog sortilin-like receptor (TgSORTLR) abolished the formation of its secretory organelles, rhoptries and micronemes.…”
Section: Methodsmentioning
confidence: 99%
“…PC12 and ␣TC1-6 cells express chromogranin A, and human ␣ cells additionally express chromogranin B and secretogranins III (34,45,46), whereas L cells express CgB and secretogranins II, III, and V (47), thus showing similarities in sorting machinery. The exocytosis machinery is also similar, with both PC12 and ␣TC1-6 cells expressing the SNARE proteins syntaxin-1a, VAMP2, SNAP25 (34,48), and the SNARE-associated proteins Munc13-1 and Munc18-1 (49, 50), whereas AP-1 and AP-3 are expressed by PC12 and mouse ␣ cells (51). More recently, it has been shown that the GLUTag L cell model also expresses SNAP25, VAMP-1, -2 and -3, syntaxin-1a, and Munc18-1 (52).…”
Section: Rationale For Using Pc12 Cells As a Model Of Hormonementioning
confidence: 99%